Example 5: Construct the language generated from the given grammar
G1 = ({S}, {a, b}, {S}, {P})
P: S → aS | bS | λ
Solutions:
There are three productions S → aS, S → bS, S → λ are combined as a whole in a given production rule of the grammar G.
Now, which type of string we can generate for this grammar:
For S → λ [We can get only empty string λ]
1) S → aS → a . λ = a [S replace by λ]
2) S → aS → abS → ab [S → bS, S → λ]
3) S → aS → abS → abaS → aba [S → bS, S → aS, S → λ]
4) S → bS → b. λ= b [S replace by λ]
5) S → bS → b. aS → ba [S → aS S → λ]
6) S → bS → b. aS → ba. bS → bab [S → aS , S → bS, S → λ]
Actually, from this grammar, we can generate all strings generated by a,b including λ.
If ∑ = {a,b} then ∑*= {λ, a, b, aa, ab, ba, bb, aaa, aab, aba, abb, baa, …} = (a + b)*
Here L(G1) = (a,b)*= {λ, a, b, aa, ab, ba, bb, aaa, aab, aba, abb, baa, …} = (a + b)*
(set of all string generated by a,b including λ)
This grammar G1 = ({S}, {a, b}, {S}, {P}), P: S → aS | bS | λ for (a + b)*
If we slightly change the production, we can get the grammar of
= {a, b, aa, ab, ba, bb, aaa, aab, aba, abb, baa, …} =
G2 = ({S}, {a, b}, {S}, {P})
S → aS | bS | a | b from this production it is clear that we never get λ i.e. language does not contain any empty string λ.
So, the Language of the grammar is L(G2) = {a, b, aa, ab, ba, bb, aaa, aab, aba, abb, baa, …}
Here L(G2) = = {a, b, aa, ab, ba, bb, aaa, aab, aba, abb, baa, …} =
(set of all string generated by a,b excluding empty string λ)
This grammar G2 = ({S}, {a, b}, {S}, {P}), P: S → aS | bS | a | b for